Comparison of the Effect of Pericapsular Nerve Group Block Combined with Lateral Femoral Cutaneous Nerve Block and Fascia Iliaca Compartment Block in Patients Undergoing Hip Arthroscopy Under General Anesthesia: A Randomized, Double-Blind Trial - Liu M; Gao M; Hu Y; Ren X; Li Y; Gao F; Dong J; Dong J; Wang Q (Journal of Pain Research, 2024)
Menglin Liu,1 Mingyang Gao,1 Yufei Hu,1 Xiaoqin Ren,1 Yanan Li,1 Fang Gao,1 Jianglong Dong,1 Jiangtao Dong,2 Qiujun Wang1 1Department of Anesthesiology, The Third Hospital of Hebei Medical University, Shijiazhuang, Hebei Province, People’s Republic of China; 2Department of Orthopaedic Surgery, The Third Hospital of Hebei Medical University, Shijiazhuang, Hebei Province, People’s Republic of ChinaCorrespondence: Qiujun Wang, Third Hospital of Hebei Medical University, No. 139, Ziqiang Road, Shijiazhuang City, Hebei, People’s Republic of China, Tel/Fax +86-311-8860-2072, Email wangqiujunsy@163.comPurpose: Patients undergoing arthroscopic hip surgery (AHS) require good analgesia and early rehabilitation after surgery, and there is no consensus on the optimal nerve block. We aimed to compare the efficacy of the pericapsular nerve group (PENG) block with lateral femoral cutaneous nerve (LFCN) block compared to fascia iliaca compartment block (FICB) in patients with AHS.Patients and Methods: A total of 80 patients receiving AHS under general anesthesia were randomized to receive either FICB (group F) or PENG block in combination with LFCN block (group P). The primary outcomes were the rate of quadriceps weakness after block on the afflicted side, as well as muscle strength grading and pain score after block, and the quality of recovery on the second postoperative day.Results: Compared with group F, group P had a lower incidence of quadriceps weakness 48 h after block (76.9% vs 28.2%, P < 0.001), and had less impact on muscle strength grade and lower static pain score at 6, 12, 18, 24, 36, and 48 h after block (P < 0.001), and a lower dynamic pain score at 6 and 12 h after block in group P (p < 0.05). The quality of recovery on the second postoperative day improved (p < 0.05).Conclusion: In comparison to FICB, PENG block in combination with LFCN block can affect less quadriceps muscle strength and reduce the use of postoperative analgesics, which is beneficial for the postoperative recovery of AHS patients.Keywords: analgesia, fascia iliaca compartment block, hip arthroscopy, nerve group block, pericapsular, postoperative pain